Pacific finance sector brief Timor-Leste. (Metro Manila, Philippines Asian Development Bank, 2019)
Timor Leste has a relatively diverse financial system for a Pacific island country. It has four foreign owned banks and one national bank, which serves as the monetary authority and regulator of most financial institutions. The finance sector also includes insurance companies, microfinance institutions, money transfer operators, financial cooperatives, and credit unions. Although Timor-Leste finance sector is progressing, some critical constraints remain. The cash based economy makes payments inefficient and insecure, and small and medium-sized enterprises and rural businesses find it challenging to access affordable credit, which constrains private sector development. Improvements in the financial regulatory environment and the creation of more diverse financial products are priorities for the sector.
Keywords: Finance -- Timor-Leste.; Industrial policy; Electronic books